Rolling method of antibacterial titanium alloy plate
By rolling a synergistic antibacterial coating on the surface of medical devices, combining the characteristics of silver nanoparticles and modified chitosan, the drug resistance and high cost of existing antibacterial technologies on the surface of medical devices is solved, and a long-term and safe antibacterial effect is achieved.
Patent Information
- Application Number
- CN202411879610.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The surface antibacterial technology of existing medical devices has problems such as drug resistance, high cost, and biotoxicity, and passive antibacterial methods cannot effectively prevent bacterial adhesion in the long term.
A rolling method for antibacterial titanium alloy sheet is adopted to form a synergistic coating by mixing antibacterial agents, modified chitosan and guar gum under specific conditions, combining the stability of silver nanoparticles and the layered structure of montmorillonite to enhance the hydrophobicity and antibacterial properties of the coating.
It achieves a long-term, safe and effective antibacterial effect on the surface of medical devices, improves the antibacterial properties and corrosion resistance of the coating, and ensures the safety and reliability of medical devices.
Smart Images

Figure BDA0005197862570000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy materials, in particular to a rolling method for an antibacterial titanium alloy plate. Background Art
[0002] Titanium alloy materials have good corrosion resistance, fatigue resistance and biocompatibility, and are widely used in the medical field, especially implantable devices. Medical devices are of various models, complex structures, small local sizes, and are exposed to a variety of media during use. They are easily attached with stains, leading to the accumulation of microorganisms and causing device infection. Safe and reliable medical devices are the key to improving treatment efficiency.
[0003] Based on the bacterial growth mechanism, the existing antibacterial modification methods for metal material surfaces are summarized into two categories: modification methods that rely on antibacterial coatings for active sterilization and modification methods that control surface wettability to passively inhibit bacterial adhesion. Although active modification methods can kill bacteria fundamentally, these bactericides have problems such as drug resistance, high cost, and biological toxicity in practical applications. Passive modification methods cannot kill bacteria directly, and once the surface is colonized by bacteria, the antibacterial effect will be lost. In order to achieve efficient, long-term, and safe cleaning of the surface of medical devices, researchers have proposed an active-passive synergistic antibacterial modification method that combines chemical sterilization methods with anti-adhesion antibacterial methods to give full play to the advantages of both methods. This is the focus of future research. Summary of the invention
[0004] The object of the present invention is to provide a rolling method for an antibacterial titanium alloy plate to solve the problems raised in the background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for rolling an antibacterial titanium alloy sheet, comprising the following steps:
[0006] The antibacterial agent, modified chitosan and guar gum are added to deionized water in sequence, soaked at 50-70°C for 2-3 hours, and then the cross-linking agent and plasticizer are added to the solution, stirred for 2-3 hours, and after removing bubbles with ultrasound, the film-forming solution is poured on a titanium alloy plate and dried to obtain an antibacterial titanium alloy plate.
[0007] Furthermore, the dosage ratio of the antibacterial agent, modified chitosan, guar gum, cross-linking agent, plasticizer and deionized water is 0.01-0.03 g: 0.2-0.6 g: 0.1-0.3 g: 0.004-0.009 g: 0.05-0.15 g: 10-40 mL.
[0008] Furthermore, the preparation method of the antibacterial agent is:
[0009] Disperse silver nitrate in deionized water, add montmorillonite, stir overnight, add 5% tea polyphenols by mass, stir at 70-90°C for 1-2h, dropwise add 0.1mol / L sodium hydroxide solution, adjust the pH to 10, dialyze in deionized water for 48h, replace the water every 12h, and then freeze-dry to obtain an antibacterial agent.
[0010] It should be noted that: in the lamellar structure of montmorillonite, tea polyphenols reduce silver nitrate into silver nanoparticles in situ and evenly disperse them inside and on the surface of montmorillonite.
[0011] Furthermore, the usage ratio of the silver nitrate, deionized water, montmorillonite and tea polyphenols is 0.01-0.05 g: 20 mL: 0.01-0.02 g: 10 mL.
[0012] Furthermore, the preparation method of the modified chitosan is:
[0013] The chitosan was dissolved in an acetic acid solution with a molar concentration of 0.2M, and ethanol was added to dilute it to obtain a mixed solution of chitosan. The pH value was adjusted to 5-5.5 with a sodium hydroxide solution with a molar concentration of 1M, and an ethanol solution of dodecyl aldehyde with a mass concentration of 25g / L was added, and the mixture was stirred evenly. Sodium cyanoborohydride was added and stirred at room temperature for 24h. The pH value was adjusted to 6-7 with a sodium hydroxide solution with a molar concentration of 1M, and then ethanol was added. The precipitate was collected, washed with ethanol, and vacuum dried to obtain modified chitosan.
[0014] It should be noted that the alkyl chain was grafted onto the amino group of the chitosan backbone through the Schiff base reaction, as shown below.
[0015]
[0016] Furthermore, the volume ratio of the chitosan mixed solution to the dodecyl aldehyde ethanol solution is 30-50:1-2.
[0017] Furthermore, the usage ratio of chitosan, acetic acid solution and ethanol solution in the chitosan mixed solution is 1-6 g: 200-250 mL: 100-200 mL.
[0018] Furthermore, the dosage of the sodium cyanoborohydride is 3 mol / chitosan single molecule; and the chitosan is shrimp shell chitosan with a molecular weight of 512 KDa.
[0019] Furthermore, the cross-linking agent is sodium tripolyphosphate.
[0020] Furthermore, the plasticizer is glycerol.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) the alkylated chitosan has a long hydrophobic chain and is tightly cross-linked with guar gum under the cross-linking action of sodium tripolyphosphate, which synergistically improves the hydrophobic effect of the coating, blocks the adhesion of moisture and bacteria, and improves the antibacterial performance and corrosion resistance of the coating; (2) tea polyphenols participate in the formation of silver nanoparticles and serve as a surface capping agent to give the nanoparticles stability; the layered morphology of montmorillonite nanosheets avoids the agglomeration of silver nanoparticles during the synthesis of silver nanoparticles, and the silver nanoparticles are uniformly dispersed on the surface of montmorillonite. At the same time, the nanosilver particles effectively increase the space between the montmorillonite sheets, increase the pore complexity of the coating, and provide a more active place for the release of silver nanoparticles, thereby improving the antibacterial ability of the coating; (3) the hydrophobicity of the coating surface hinders the adhesion and entry of bacteria and moisture, and the chitosan and silver nanoparticles inside the coating have bactericidal and antibacterial properties. Through the effective combination of the two antibacterial effects, the antibacterial effect of the coating is fully exerted, and at the same time, the titanium alloy plate can be protected and its corrosion resistance can be improved. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] The invention provides a technical solution: a rolling method for an antibacterial titanium alloy plate.
[0024] Example 1
[0025] S1. Disperse 0.034 g of silver nitrate in 20 mL of deionized water, add 0.01 g of montmorillonite, stir overnight, then add 10 mL of 5% tea polyphenol solution, drop 0.1 mol / L sodium hydroxide solution, adjust the pH to 10, stir at 80 ° C for 1 h, dialyze in deionized water for 48 h, change the water every 12 h, and then freeze-dry to obtain an antibacterial agent;
[0026] S2, 4g chitosan was dissolved in 220mL 0.2M acetic acid solution, then diluted with 150mL ethanol to obtain a mixed solution of chitosan, and the pH value was adjusted to 5.1 with 1M sodium hydroxide solution, 10mL of an ethanol solution of dodecyl aldehyde was added with 25g / L, stirred, sodium cyanoborohydride (3 mol / chitosan monomer) was added, and stirred at room temperature for 24h, 1M sodium hydroxide solution was used to adjust the pH to 7, then ethanol was added, and the precipitate was collected and washed with ethanol. After vacuum drying at room temperature, modified chitosan was obtained;
[0027] S3. Add 0.02g of antibacterial agent, 0.4g of modified chitosan and 0.2g of guar gum into 20mL of deionized water in sequence, soak in a water bath at 60°C for 2h, then add 0.006g of sodium tripolyphosphate and 0.1g of glycerol into the solution, stir for 2h, remove bubbles with ultrasound, pour the film-forming solution onto a titanium alloy plate, and dry at room temperature to obtain an antibacterial titanium alloy plate.
[0028] Example 2
[0029] S1. Disperse 0.04 g of silver nitrate in 25 mL of deionized water, add 0.02 g of montmorillonite, stir overnight, then add 15 mL of 5% tea polyphenol solution, drop 0.1 mol / L sodium hydroxide solution, adjust the pH to 10, stir at 80 ° C for 1 h, dialyze in deionized water for 48 h, change the water every 12 h, and then freeze-dry to obtain an antibacterial agent;
[0030] S2, 4.5g chitosan was dissolved in 230mL 0.2M acetic acid solution, then diluted with 150mL ethanol, obtained a mixed solution of chitosan, and with 1M sodium hydroxide solution, the pH value was adjusted to 5.1, 25g / L was added into 15mL of an ethanol solution of dodecyl aldehyde, stirred, sodium cyanoborohydride (3 mol / chitosan monomer) was added, and stirred at room temperature for 24h, 1M sodium hydroxide solution was used to adjust the pH to 7, then ethanol was added, and precipitate was collected, washed with ethanol, and after vacuum drying at room temperature, modified chitosan was obtained;
[0031] S3. Add 0.025g of antibacterial agent, 0.45g of modified chitosan and 0.25g of guar gum to 25mL of deionized water in sequence, soak in a water bath at 60°C for 2h, then add 0.005g of sodium tripolyphosphate and 0.15g of glycerol to the solution, stir for 2h, remove bubbles with ultrasound, pour the film-forming solution on a titanium alloy plate, and dry at room temperature to obtain an antibacterial titanium alloy plate.
[0032] Example 3
[0033] S1. Disperse 0.04 g of silver nitrate in 25 mL of deionized water, add 0.02 g of montmorillonite, stir overnight, then add 20 mL of 5% tea polyphenol solution, drop 0.1 mol / L sodium hydroxide solution, adjust the pH to 10, stir at 80 ° C for 1 h, dialyze in deionized water for 48 h, change the water every 12 h, and then freeze-dry to obtain an antibacterial agent;
[0034] S2, 5g chitosan was dissolved in 250mL 0.2M acetic acid solution, then diluted with 160mL ethanol to obtain a mixed solution of chitosan, and the pH value was adjusted to 5.1 with 1M sodium hydroxide solution, 16mL of an ethanol solution of dodecyl aldehyde was added with 25g / L, stirred, sodium cyanoborohydride (3 mol / chitosan monomer) was added, and stirred at room temperature for 24h, 1M sodium hydroxide solution was used to adjust the pH to 7, then ethanol was added, and the precipitate was collected, washed with ethanol, and after vacuum drying at room temperature, modified chitosan was obtained;
[0035] S3. Add 0.03g of antibacterial agent, 0.5g of modified chitosan and 0.3g of guar gum to 30mL of deionized water in sequence, soak in a water bath at 60°C for 2h, then add 0.007g of sodium tripolyphosphate and 0.12g of glycerol to the solution, stir for 2h, remove bubbles with ultrasound, pour the film-forming solution on a titanium alloy plate, and dry at room temperature to obtain an antibacterial titanium alloy plate.
[0036] Example 4
[0037] S1. Disperse 0.05 g of silver nitrate in 15 mL of deionized water, add 0.01 g of montmorillonite, stir overnight, then add 15 mL of 5% tea polyphenol solution, drop 0.1 mol / L sodium hydroxide solution, adjust the pH to 10, stir at 80 ° C for 1 h, dialyze in deionized water for 48 h, change the water every 12 h, and then freeze-dry to obtain an antibacterial agent;
[0038] S2, 5.5g chitosan was dissolved in 280mL 0.2M acetic acid solution, then diluted with 180mL ethanol, obtained a mixed solution of chitosan, and with 1M sodium hydroxide solution, the pH value was adjusted to 5.1, 25g / L was added into 20mL of an ethanol solution of dodecyl aldehyde, stirred, sodium cyanoborohydride (3 mol / chitosan monomer) was added, and stirred at room temperature for 24h, 1M sodium hydroxide solution was used to adjust the pH to 7, then ethanol was added, and precipitate was collected, washed with ethanol, and after vacuum drying at room temperature, modified chitosan was obtained;
[0039] S3. Add 0.02g of antibacterial agent, 0.55g of modified chitosan and 0.3g of guar gum to 30mL of deionized water in sequence, soak in a water bath at 60°C for 2h, then add 0.008g of sodium tripolyphosphate and 0.1g of glycerol to the solution, stir for 2h, remove bubbles with ultrasound, pour the film-forming solution on the titanium alloy plate, and dry at room temperature to obtain an antibacterial titanium alloy plate.
[0040] Comparative Example 1
[0041] S1. Disperse 0.034 g of silver nitrate in 20 mL of deionized water, add 0.01 g of montmorillonite, stir overnight, then add 10 mL of 5% tea polyphenol solution, drop 0.1 mol / L sodium hydroxide solution, adjust the pH to 10, stir at 80 ° C for 1 h, dialyze in deionized water for 48 h, change the water every 12 h, and then freeze-dry to obtain an antibacterial agent;
[0042] S2. Add 0.02g of antibacterial agent, 0.4g of chitosan and 0.2g of guar gum to 20mL of deionized water in sequence, soak in a water bath at 60°C for 2h, then add 0.006g of sodium tripolyphosphate and 0.1g of glycerol to the solution, stir for 2h, remove bubbles with ultrasound, pour the film-forming solution on a titanium alloy plate, and dry at room temperature to obtain an antibacterial titanium alloy plate.
[0043] Comparative Example 2
[0044] S1, 4g chitosan was dissolved in 220mL 0.2M acetic acid solution, then diluted with 150mL ethanol to obtain a mixed solution of chitosan, and the pH value was adjusted to 5.1 with 1M sodium hydroxide solution, 10mL of ethanol solution of 25g / L dodecyl aldehyde was added, stirred evenly, sodium cyanoborohydride (3 mol / chitosan monomer) was added, and stirred at room temperature for 24h, 1M sodium hydroxide solution was used to adjust the pH to 7, then ethanol was added, the precipitate was collected, washed with ethanol, and after vacuum drying at room temperature, modified chitosan was obtained;
[0045] S3. Add 0.002g of silver nanoparticles, 0.4g of modified chitosan and 0.2g of guar gum to 20mL of deionized water in sequence, soak in a water bath at 60°C for 2h, then add 0.006g of sodium tripolyphosphate and 0.1g of glycerol to the solution, stir for 2h, remove bubbles with ultrasound, pour the film-forming solution on a titanium alloy plate, and dry at room temperature to obtain an antibacterial titanium alloy plate.
[0046] Comparative Example 3
[0047] S1, 4g chitosan was dissolved in 220mL 0.2M acetic acid solution, then diluted with 150mL ethanol to obtain a mixed solution of chitosan, and the pH value was adjusted to 5.1 with 1M sodium hydroxide solution, 10mL of ethanol solution of 25g / L dodecyl aldehyde was added, stirred evenly, sodium cyanoborohydride (3 mol / chitosan monomer) was added, and stirred at room temperature for 24h, 1M sodium hydroxide solution was used to adjust the pH to 7, then ethanol was added, the precipitate was collected, washed with ethanol, and after vacuum drying at room temperature, modified chitosan was obtained;
[0048] S3. Add 0.4 g of modified chitosan and 0.2 g of guar gum to 20 mL of deionized water in sequence, soak in a water bath at 60°C for 2 h, then add 0.006 g of sodium tripolyphosphate and 0.1 g of glycerol to the solution, stir for 2 h, remove bubbles with ultrasound, pour the film-forming solution on a titanium alloy plate, and dry at room temperature to obtain an antibacterial titanium alloy plate.
[0049] Comparative Example 4
[0050] 0.4 g of chitosan and 0.2 g of guar gum were added to 20 mL of deionized water in sequence and soaked in a water bath at 60°C for 2 h. Subsequently, 0.006 g of sodium tripolyphosphate and 0.1 g of glycerol were added to the solution and stirred for 2 h. After removing bubbles with ultrasound, the film-forming solution was poured onto a titanium alloy plate and dried at room temperature to obtain an antibacterial titanium alloy plate.
[0051] The performance of each embodiment and the comparative example was tested experimentally; the antibacterial properties of the samples were tested by the inhibition zone (ZOI) and colony counting methods, Escherichia coli and Staphylococcus aureus were selected as reference strains for the antibacterial test, for ZOI, the nutrient agar medium in the culture dish was inoculated with 100 μL of 107-108 CFU / mL of bacteria, a titanium alloy plate was placed on the culture dish, and the bacteria were cultured at 37°C for 24 hours, and then the diameter of the inhibition zone was determined, and 3 replicates were tested for each sample; the static water contact angle was measured by a contact angle goniometer using the sessile drop method, the image of water spreading on the sample surface was recorded by a camera, the contact angle was analyzed by professional software, and each sample was measured three times; according to the ISO2782 standard, the film was subjected to a nitrogen permeability test on a gas permeability measuring device.
[0052] The test results are shown in Table 1.
[0053] Table 1: Experimental results of various embodiments and comparative examples
[0054] sample Antibacterial rate (%) Water contact angle (degrees) <![CDATA[Permeability × 10 -17 (m 2 ·s -1 ·Pa -1 )]]> Example 1 99.8 148.7 3.91 Example 2 99.5 145.8 4.02 Example 3 99.1 141.5 4.11 Example 4 98.9 139.9 4.21 Comparative Example 1 80.6 126.7 5.36 Comparative Example 2 72.4 123.7 5.70 Comparative Example 3 51.7 120.6 5.84 Comparative Example 4 37.9 109.2 6.31
[0055] According to the experimental results, the antibacterial and bactericidal properties of the silver nanoparticles and chitosan in the embodiment and the close cross-linked network formed by the hydrophobically modified chitosan and guar gum improve the hydrophobicity of the coating, and the two antibacterial effects synergistically promote the antibacterial properties of the coating as a whole. In addition, the layered structure of montmorillonite further helps the dispersion of silver nanoparticles, and also provides more active sites, helping to form a complex cross-linked system, blocking the entry of moisture and bacteria, and also improving the corrosion resistance of the titanium alloy sheet. In the comparative example, the silver nanoparticles may be aggregated, affecting its antibacterial effect, and the chitosan and guar gum without introducing the hydrophobic long chain are cross-linked, and its hydrophobic properties are worse than those of the embodiment. In addition, antibacterial is carried out by the way of hydrophobic coating, and only chitosan has certain antibacterial properties inside the coating, and the overall effect is not as good as that of the embodiment.
[0056] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for rolling an antibacterial titanium alloy sheet, characterized in that: The following steps are involved: The antibacterial agent, modified chitosan and guar gum are added to deionized water in sequence, soaked at 50-70°C for 2-3 hours, and then the cross-linking agent and plasticizer are added to the solution, stirred for 2-3 hours, and after removing bubbles with ultrasound, the film-forming solution is poured on a titanium alloy plate and dried to obtain an antibacterial titanium alloy plate.
2. The rolling method of an antibacterial titanium alloy sheet according to claim 1, characterized in that: The dosage ratio of the antibacterial agent, modified chitosan, guar gum, cross-linking agent, plasticizer and deionized water is 0.01-0.03g: 0.2-0.6g: 0.1-0.3g: 0.004-0.009g: 0.05-0.15g: 10-40mL.
3. The rolling method of an antibacterial titanium alloy sheet according to claim 1, characterized in that: The preparation method of the antibacterial agent is: Disperse silver nitrate in deionized water, add montmorillonite, stir overnight, add 5% tea polyphenols by mass, stir at 70-90°C for 1-2h, dropwise add 0.1mol / L sodium hydroxide solution, adjust the pH to 10, dialyze in deionized water for 48h, replace the water every 12h, and then freeze-dry to obtain an antibacterial agent.
4. The rolling method of the antibacterial titanium alloy sheet according to claim 3, characterized in that: The usage ratio of the silver nitrate, deionized water, montmorillonite and tea polyphenols is 0.01-0.05 g: 20 mL: 0.01-0.02 g: 10 mL.
5. The rolling method of the antibacterial titanium alloy sheet according to claim 1, characterized in that: The preparation method of the modified chitosan is: The chitosan was dissolved in an acetic acid solution with a molar concentration of 0.2M, and ethanol was added to dilute it to obtain a mixed solution of chitosan. The pH value was adjusted to 5-5.5 with a sodium hydroxide solution with a molar concentration of 1M, and an ethanol solution of dodecyl aldehyde with a mass concentration of 25g / L was added, and the mixture was stirred evenly. Sodium cyanoborohydride was added and stirred at room temperature for 24h. The pH value was adjusted to 6-7 with a sodium hydroxide solution with a molar concentration of 1M, and then ethanol was added. The precipitate was collected, washed with ethanol, and vacuum dried to obtain modified chitosan.
6. The method for rolling an antibacterial titanium alloy sheet according to claim 5, characterized in that: The volume ratio of the chitosan mixed solution to the dodecyl aldehyde ethanol solution is 30-50:1-2.
7. The rolling method of the antibacterial titanium alloy sheet according to claim 5, characterized in that: The usage ratio of chitosan, acetic acid solution and ethanol solution in the chitosan mixed solution is 1-6g: 200-250mL: 100-200mL.
8. The method for rolling an antibacterial titanium alloy sheet according to claim 5, characterized in that: The dosage of the sodium cyanoborohydride is 3 mol / chitosan single molecule; the chitosan is shrimp shell chitosan with a molecular weight of 512 KDa.
9. The rolling method of the antibacterial titanium alloy sheet according to claim 1, characterized in that: The cross-linking agent is sodium tripolyphosphate.
10. The rolling method of the antibacterial titanium alloy sheet according to claim 1, characterized in that: The plasticizer is glycerol.
Citation Information
Patent Citations
Antibacterial chitosan-based hemostatic patch
CN112791223A
Ag NPS-oxidized tea polyphenol-acrylic acid hydrogel as well as preparation and application of Ag NPS-oxidized tea polyphenol-acrylic acid hydrogel
CN114504675A
Traceless silica gel patch with antibacterial effect
CN115109560A
Modified chitosan / Ag nanoparticle composite material as well as preparation method and application thereof
CN117065081A
Chitosan dispersion polymer and coating composition containing the same
JP2007238692A